2018
DOI: 10.1021/acs.biochem.7b00557
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biophysical Characterization of Human EXTL3: Domain Organization, Glycosylation, and Solution Structure

Abstract: Heparan sulfate proteoglycans are proteins substituted with one or more heparan sulfate (HS) polysaccharides, found in abundance at cell surfaces. HS chains influence the activity of many biologically important molecules involved in cellular communication and signaling. The exostosin (EXT) proteins are glycosyltransferases in the Golgi apparatus that assemble HS chains on HSPGs. The EXTL3 enzyme mainly works as an initiator in HS biosynthesis. In this work, human lumenal N-glycosylated EXTL3 (EXTL3ΔN) was clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…It has been shown to exhibit GlcNAc transferase I and II activities. Since the glycosyltransferase domain on the N-terminal side (GT47) of EXT1/EXT2 was predicted to be GlcA transferase II, based on a bioinformatics analysis [32], the GT47 domain of EXTL3 may exhibit no enzyme activity. The GT64 domain in EXTL3 appears to have both GlcNAc transferase I and II activities.…”
Section: Characteristics Of the Extl3 Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown to exhibit GlcNAc transferase I and II activities. Since the glycosyltransferase domain on the N-terminal side (GT47) of EXT1/EXT2 was predicted to be GlcA transferase II, based on a bioinformatics analysis [32], the GT47 domain of EXTL3 may exhibit no enzyme activity. The GT64 domain in EXTL3 appears to have both GlcNAc transferase I and II activities.…”
Section: Characteristics Of the Extl3 Proteinmentioning
confidence: 99%
“…The conformation of the EXTL3 protein was recently characterized [32]. Awad et al prepared the human EXTL3 protein without the sequence for the N-terminal cytosolic and transmembrane regions (EXTL3ΔN) and examined its stability and conformation.…”
Section: Characteristics Of the Extl3 Proteinmentioning
confidence: 99%
“…5) (Kellokumpu, Hassinen, & Glumoff, 2016). The physical characteristics of EXTL proteins have been demonstrated based on the crystallographic structures of EXTL2 (Pedersen et al, 2003) and EXTL3 (Awad, Kjellstrom, Svensson Birkedal, Mani, & Logan, 2018) that exhibit similarly conserved cysteine amino acid residues in their catalytic domains (Zak, Crawford, & Esko, 2002). EXTL2 is the smallest member with 330 amino acid (a.a) residues followed by EXTL1 (676 a.a.), EXT2 (718 a.a.), EXT1 (746 a.a.) and EXTL3 is the largest with about 919 a.a. residues (Busse-Wicher et al, 2014).…”
Section: The Ext-familymentioning
confidence: 99%
“…The crystal structure revealed that EXTL2 exists as a symmetric homodimer, and that the GT64 domain adopts a GT-A fold, binding UDP-GlcNAc or UDP-GalNAc with the aid of a manganese cofactor. While the GT47 domain of the larger exostosins has been tentatively predicted to adopt a GT-B fold 30 , the overall bi-domain structure remains to be determined, and the GT47 fold is yet to be described. This missing information could provide insight into the mechanism of HS chain extension and the diverse activities of GT47 family members in plants 17 , 31 .…”
Section: Introductionmentioning
confidence: 99%